2003
DOI: 10.1007/s00122-003-1481-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular tagging of erucic acid trait in oilseed mustard (Brassica juncea) by QTL mapping and single nucleotide polymorphisms in FAE1 gene

Abstract: Molecular mapping and tagging of the erucic acid trait (C22:1) in Brassica juncea was done by a candidate gene approach. Two QTLs underlying the variation of seed erucic acid content were assigned to two linkage groups of a B. juncea map using a doubled haploid (DH) mapping population derived from high x low erucic acid F(1) hybrid. Two consensus primers corresponding to the full-length Fatty Acid Elongase 1 ( FAE1) gene, reported to be involved in the elongation of C18:1 to C22:1, were designed. PCR amplifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
55
0
2

Year Published

2005
2005
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 28 publications
8
55
0
2
Order By: Relevance
“…Qiu et al (2006) reported seven QTL and Ecke et al (1995) reported three QTLs associated with oil content in B. napus. In both studies QTL showed close linkage to the 22:1n9 genes fatty acid elongase1.1 (FAE1.1) and FAE1.2, and a similar situation has been reported for B. juncea (Thormann et al, 1996;Cheung et al, 1998;Gupta et al, 2004). Genetic characterization of the loci involved in 18:1n9 content has been carried out in B. napus, B. rapa (Tanhuanpaa et al, 1998), and B. juncea (Sharma et al, 2002).…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Qiu et al (2006) reported seven QTL and Ecke et al (1995) reported three QTLs associated with oil content in B. napus. In both studies QTL showed close linkage to the 22:1n9 genes fatty acid elongase1.1 (FAE1.1) and FAE1.2, and a similar situation has been reported for B. juncea (Thormann et al, 1996;Cheung et al, 1998;Gupta et al, 2004). Genetic characterization of the loci involved in 18:1n9 content has been carried out in B. napus, B. rapa (Tanhuanpaa et al, 1998), and B. juncea (Sharma et al, 2002).…”
supporting
confidence: 55%
“…Closely related orthologs of these genes have been isolated from Brassica species. The B. napus genes FAE1.1 and FAE1.2 have been shown to cosegregate with two loci that govern 22:1n9 production (Barret et al, 1998;Fourmann et al, 1998), with FAE1 genes also being isolated from B. oleracea and B. rapa (Das et al, 2002) as well as B. juncea (Gupta et al, 2004). Between four and six copies of FAD2 have been reported for B. napus (Scheffler et al, 1997) and representative orthologous genes encoding for both FAD2 and FAD3 have been cloned (Arondel et al, 1992;Okuley et al, 1994).…”
mentioning
confidence: 99%
“…Meanwhile, in the BC 1 progenies, some plants displayed additive patterns from both parents and some had only one specific band from S. alba, demonstrating segregation in the BC 1 progenies. The fae1 gene has been shown to be the candidate gene for elongation of C 18:1 to C 22:1 (Gupta et al 2004). It has been suggested that the variation at the erucic acid level is due to differences in the fae1 gene from the low and high erucic acid genotypes (Das et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of seed set was measured by the number of seeds obtained per pollinated flower. 1.2.6 Characterization of fae1 gene To clone the full-length fae1 gene from plants of the fusion parents, hybrids, and their progenies, primers were designed according to sequences (Gupta et al 2004). The PCR was performed in a final volume of 20 µL containing 10 ng genomic DNA, 2.5 mmol/L MgCl 2 , 0.2 mmol/L of each dNTP, 0.2 µmol/L of each primer, 1 unit HotStarTaq DNA polymerase and 1×Taq polymerase buffer as follows: 15 min at 95 °C, 35 cycles of 30 s at 94 °C, 30 s at 56 °C, 45 s at 72 °C, and 10 min at 72°C…”
Section: Mitotic and Meiotic Analysismentioning
confidence: 99%
“…Recently, quantitative trait locus (QTL) mapping has been conducted on oilseed rape to dissect the effects of individual loci for seed traits in terms of rape-oil yield (Tanhuanpää et al, 1996;Thormann et al, 1996;Zhao et al, 2005). QTL analysis in which the molecular marker near the available locus can be screened is important in molecular breeding strategies such marker associated selection (MAS) used to screen the target materials precisely and improve selection efficiency for quantitative traits (Tanhuanpää et al, 1996;Somers et al, 1998;Gupta et al, 2004). So far, QTL mapping for seed traits has been based on the maternal plant because of the QTL method used to map agriculturally plant traits.…”
Section: Discussionmentioning
confidence: 99%